Immoral in principle, unworkable in practice: cannabis law reform, the Beatles and the Wootton report - Seddon, Toby (The British journal of criminology, 2020)
In the late 1960s, the cause of cannabis law reform briefly rose to remarkable cultural prominence in several Western countries, notably the United Kingdom and the United States. Some 50 years later, as global cannabis prohibition is once again coming under intense critical scrutiny in many parts of the world, this paper revisits the events of the 1960s. Drawing on primary archival research, the paper recovers the story of the rapid emergence and development of the reform movement. The importance to reform discourse of ideas of personal freedom and civil liberties is explored and set in the context of wider shifts in liberal governance. In conclusion, it is argued that the challenge of cannabis regulation today needs to be understood in the context of contemporary regulatory capitalism.